The social readjustment rating scale: A cross-cultural study of Malaysians and Americans - Woon, Tai Hwang; Masuda, Minoru; Wagner, Nathaniel N.; Holmes, Thomas H. (SAGE Publications, 1971)
Two hundred sixty-six Malaysian medical students were compared with 195 selectively matched Americans on the Social Readjustment Rating Questionnaire. There was a remarkable concordance (Spearman's rho ranged from. 97 to. 91) between the Malaysian and American samples as well as between discrete subgroups in the Malaysian sample in the manner in which they established a relative order of magnitude to changes in life events. Some interesting and profound differences resulting from cultural variations were also observed. Attitudes of the Malaysians toward infringement of laws, the idea of romantic love and thus relationship between spouses seem to differ significantly from the American sample. Malaysians scored significantly higher on items pertaining to personal habits, religious activities, attitudes toward work, and financial security. Differences among Malaysian subgroups (race, religion, sex, year of medical class, and generation Malaysian) were discussed. © 1971, Sage Publications. All rights reserved.